Cover crops, hormones and herbicides: Priming an integrated weed management strategy. (December 2020) - Oliveira, Maxwel C.; Osipitan, O. Adewale; Begcy, Kevin; Werle, Rodrigo
Graphical abstract: Highlights: Herbicide weed resistance has been a major threat to global agriculture for decades. Most strategies adopted currently to address weed resistance are herbicide-based. A novel approach is proposed herein which integrates cover cropping with preemergence herbicides combined with a hormone (gibberellic acid) inducing synchronous weed seed germination (termed weed seed priming). Alternatively, similar approach with abscisic acid instead, which enhances weed seed dormancy. These strategies have the potential to reduce the need for postemergence herbicides, slowing down herbicide weed resistance evolution while enhancing sustainability of agricultural systems. Abstract: Herbicide weed resistance has been a major issue of conventional global row crop agriculture for decades. Still current strategies and novel technologies available to address weed resistance are mainly herbicide-based. Thus, there is a need for innovative means of integrated weed management strategies. Our approach proposed herein integrates cover crops, plant hormones and pre-emergence (PRE) herbicides as part of weed management programs. Plant hormones such as gibberellic acid (GA3 ) and abscisic acid (ABA) have the potential to induce seed germination and seed dormancy, respectively. Prior to crop emergence, plant hormones are tank mixed with PRE herbicides and sprayed to cover crop residue. Two strategies are proposed (1) PRE herbicides + GA3 and (2) PRE herbicide + ABA. The hormones provide different results; GA3 is likely to stimulate a more uniform weed seed germination, thus enhancing efficacy of PRE herbicides. Conversely, ABA could promote weed seed dormancy, reducing selection pressure and weed infestations until crop canopy closure. Much research is needed to understand the impact of hormones on weed and crop species, optimize products and rates, and compatibility of hormones with herbicides and cover crops. If successful, this approach could open a new opportunity for agricultural business, enhance farming sustainability by reducing dependence on herbicides and minimizing agronomic, economic and environmental issues related to weed resistance.